The importance of unsaturated soil properties in the development of slope susceptibility map for Old Alluvium in Singapore - Rahardjo Harianto; Li Yangyang; Satyanaga Alfrendo (E3S Web of Conferences, 2023)
Slope failures caused by rainfall are a regular occurrence in residual soils. As a result of climate change, increased precipitation is anticipated; preventing slope failures due to rain is therefore essential. One typical technique for pinpointing regions at risk for slope failures is the use of a “slope susceptibility map.” Because the groundwater table is usually deep, many slopes in residual soil are typically unsaturated. Soil-water characteristic curve, permeability function, and unsaturated shear strength are the essential unsaturated soil parameters that should be factored into the creation of a slope susceptibility map. This research involved the Old Alluvium region in Singapore as a case study. Transient rainfall infiltration and grid-based regional slope stability (TRIGRS) model was used to establish pore-water pressure distributions over this region. Scoops3D was utilized to include the pore-water pressures calculated by TRIGRS for evaluating slope stability in three dimensions. To assess the reliability of the developed slope susceptibility map, two-dimensional (2-D) numerical analyses were performed on a subset of historically unstable residual soil slopes at the Bidadari site. Minimum safety factors determined via numerical analyses of the slopes under study agreed well with those determined via the slope susceptibility map.